Negative entropy of halothane binding to protein: 19F-NMR with a novel cell - Yoshida, Tadayoshi; Tanaka, Masaki; Mori, Yoshihito; Ueda, Issaku (Biochimica et biophysica acta, 1997)
An obvious difficulty of the study of binding of volatile anesthetics to proteins is to prevent loss of the ligand during the procedure. A novel NMR tube was designed that consists of concentric double cylinders which slide each other under sealed condition. A gas space is left in the tube to measure the free anesthetic concentration in the gas phase, which is in equilibrium with the solution. The enthalpy change of anesthetic transfer from water to BSA, ΔH w→r, was −40 kJ·mol −1. The Gibbs free energy ΔG w→r was −14.0 kJ·mol −1 at 283 K ( K D=2.6 mM) and increased to −11.6 kJ·mol −1 at 310 K ( K D=10.9 mM). The maximum binding site ( B max) was 19.3 at 10°C and increased to 34.5 at 37°C. The entropy change, ΔS w→r, was −92 J·mol −1· K −1 and was almost constant in the temperature range 10∼37°C. Contrary to the general consensus that hydrophobic interaction is entropy-driven, the binding of halothane to BSA was enthalpy-driven, compensating the opposing effect of ΔS with negative ΔH at the biologically meaningful temperature range. Possible cause of the negative ΔS relating to the conformational change of BSA is discussed.